Distribution, prevalence, and antibiotic susceptibility profiles of infectious noncholera Vibrio species in Malaysia - Hassan, Murnihayati; Mohd Ali, Mohammad Ridhuan; Zamri, Hana Farizah; Nor Amdan, Nur Asyura; Azmai, Mohammad Noor Amal; Maniam, Saraswathiy; Mohamed Alipiah, Norfarrah; Hashim, Rohaidah (Hindawi, 2023)
The noncholera Vibrio spp. which cause vibriosis are abundantly found in our water ecosystem. Tese bacteria could negatively afect both humans and animals. To date, there is a paucity of information available on the existence and pathogenicity of this particular noncholera Vibrio spp. in Malaysia in comparison to their counterpart, Vibrio cholera. Methods. In this study, we extracted retrospective data from Malaysian surveillance database. Analysis was carried out using WHONET software focusing noncholera Vibrio spp. including Vibrio parahaemolyticus, Vibrio vulnifcus, Vibrio fuvialis, Vibrio alginolyticus, Vibrio hollisae (Grimontia hollisae), Vibrio mimicus, Vibrio metschnikovii, and Vibrio furnissii. Results. Here, we report the frst distribution and prevalence of these species isolated in Malaysia together with the antibiotic sensitivity profle based on the species. We found that V. parahaemolyticus is the predominant species isolated in Malaysia. Noticeably, across the study period, V. fuvialis is becoming more prevalent, as compared to V. parahaemolyticus. In addition, this study also reports the frst isolation of pathogenic V. furnissii from stool in Malaysia. Conclusion. Tese data represent an important step toward understanding the potential emergence of noncholera Vibrio spp. outbreaks.